STAT3 inhibition reverses neuroinflammation and Aβ metabolism induced by systemic inflammation: Molecular and cell biology/neuroinflammation. (7th December 2020) - Millot, Perine; San, Carine; Bennana, Evangeline; Hugon, Jacques; Paquet, Claire; Hosten, Benoit; Mouton‐Liger, Francois
Abstract: Background: STAT3 is a transcriptional factor involved in various physiological processes, including immune reaction. Abnormal activation of the, STAT3, has been recently associated with Alzheimer Disease (AD). Phosphorylation of STAT3 is dramatically increased in the hippocampus of AD mouse model and in AD post‐mortem brain. STAT3 phosphorylation is critical for cytokines secretion known to be involved in neuroinflammation, such as Il‐1β, IL‐6 or TNF‐α. Moreover, STAT3 may act as a transcriptional regulator of BACE1, the key enzyme in amyloïd β (Aβ) production. Our group have previously shown that neuroinflammation and increased brain Aβ production induced by systemic inflammation in wild‐type (WT) mice is associated with an excessive activation of STAT3 (Rebillat et al., 2015). Inhibitors of STAT3 have already shown beneficial effects in several pathology, such as cancer. The main objective of this research project was to investigate if STAT3 inhibitors could reverse neuroinflammation and abnormal BACE1 regulation in vivo and be considered as potential drug candidates for treatment in AD. Method: C57BL/6 wild type mice were injected intraperitoneally with LPS (1mk/kg) versus saline once a day for 3 days to induce neuroinflammation and STAT3 activation. Inhibition of STAT3 activation is mediated by intraperitoneal injection of STATTIC, a small molecule which selectively inhibits dimerization and nuclear translocation of STAT3. Brains were collected and dissected; immunohistochemistry and western blotting were performed for neuroinflammation, STAT3 activation and Aβ metabolism (as BACE1 level). Result: STATTIC injection significantly decreases LPS‐induced microglial activation in the hippocampus. In addition, STAT3 inhibition reduces production of cytokines IL‐6, IL‐10 and TNF‐α triggered by LPS administration. We also observed a significative reduction of BACE1 level in the hippocampus of mice treated with LPS and STATTIC compared to those exposed to LPS alone. Conclusion: Taking together, our results show that STATTIC can reverse neuroinflammation and BACE1‐Aβ signaling deregulation induced by systemic inflammation, and pave the way for further explorations of the therapeutic potential of STAT3 inhibition in AD.